2005
DOI: 10.1186/1465-9921-6-47
|View full text |Cite|
|
Sign up to set email alerts
|

Short-term variability of biomarkers of proteinase activity in patients with emphysema associated with type Z alpha-1-antitrypsin deficiency

Abstract: We found acceptable variability in our study parameters, indicating the feasibility of their use in an evaluation of biochemical efficacy of alpha-1-antitrypsin augmentation therapy in Pi Z subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The high correlation between urinary and plasma desmosines [45] is consistent with the correlation between urinary and plasma elastin peptides previously reported [9], thus suggesting that plasma and urine generally provide comparable estimates of elastin turnover. The correlation of individual values for plasma and urine levels of desmosines performed by STOLK et al [45] also diminishes the concern, based on previous experimental findings, that the kidney may sequester elastin peptides and release them over an extended period of time [50]: urinary DES excretion would reflect the changes in blood levels of elastin degradation products, although with more variability.…”
Section: Desmosine and Copd: Established Concepts Unresolved Issues supporting
confidence: 75%
See 3 more Smart Citations
“…The high correlation between urinary and plasma desmosines [45] is consistent with the correlation between urinary and plasma elastin peptides previously reported [9], thus suggesting that plasma and urine generally provide comparable estimates of elastin turnover. The correlation of individual values for plasma and urine levels of desmosines performed by STOLK et al [45] also diminishes the concern, based on previous experimental findings, that the kidney may sequester elastin peptides and release them over an extended period of time [50]: urinary DES excretion would reflect the changes in blood levels of elastin degradation products, although with more variability.…”
Section: Desmosine and Copd: Established Concepts Unresolved Issues supporting
confidence: 75%
“…GOTTLIEB et al [26] found a significant correlation between urinary DES and FEV1 decline in smokers. In a short-term longitudinal study in PI*ZZ individuals with emphysema, STOLK et al [45] could not detect any relationship between plasma or urinary desmosines and FEV1, whereas a significant correlation was found between plasma desmosines (p,0.01) and urinary desmosines (p,0.05) and KCO. In a subsequent investigation of a larger group of patients with emphysema associated with AATD, the lack of significant correlation between urinary desmosines and FEV1 was confirmed, but a significant correlation (r50.57, p50.018) between urinary desmosines and phase III of the single-breath nitrogen test was also demonstrated [52].…”
Section: Desmosine and Copd: Established Concepts Unresolved Issues mentioning
confidence: 99%
See 2 more Smart Citations
“…In COPD, the high prevalence of emphysema in patients with ␣ 1 -AT deficiency, particularly in smokers, is believed to be caused by the unchecked action of serine proteases on lung tissue (Laurell and Eriksson, 1963). Lung lavage studies reveal that these patients have an increased number of neutrophils, increased levels of plasma and urinary desmosine (a biomarker of elastin tissue breakdown) correlated to carbon monoxide diffusion capacity (Stolk et al, 2005), and a greater NE burden in the lower airways (Morrison et al, 1987). There is also a positive correlation between the local distribution of NE in contact with alveolar interstitial elastin and the presence of emphysematous changes in COPD lung tissue (Damiano et al, 1986).…”
Section: Introductionmentioning
confidence: 99%